IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING PUZZLE GAME AT THE SECOND GRADE OF MTS AL-WASHLIYAH MEDAN - Lailatul Munawaroh Panjaitan; Dwi Suci Amaniarsih (Journal MELT (Medium for English Language Teaching), 2021)
This research was conducted at Mts AL-Washliyah Medan. The background of this research is base on the fact that the second grade of students AL-Washliyah Medan, teacher still used conventional methods and students achievement is still low and needs to be improved. The use of Puzzle Game as a method is very effective and can increase students motivation in learning. Students more interested and happy when learning English. The Objectives of this study were as follows: To describe the increase in students’ vocabulary by using Puzzle Game for seacond grade of Mts- AL-Washliyah Medan, to determine the increase in students’ vocabulary after using the Puzzle Game. And the results showed that in the pre-cycle the students score was 63,2. In cycle I the students score was 66,8. In cycle II, the students score was 73,2. There has been an increase in students’ vocabulary skills in each cycle. Using Puzzle Game can make students more interested and motivated in learning. The conclusion, Puzzle Game was effectived for improving students’ vocabulary.